Internet of things with NodeMCU ESP8266 for MPX-5700AP sensor-based LPG pressure monitoring - Tole Sutikno; Muhamad Haikal Ar-Rasyid; Tri Wahono; Watra Arsadiando (Institute of Advanced Engineering and Science, 2023)
The use of liquefied petroleum gas (LPG) cylinders as fuel has become a basic need for the community. LPG is more efficient than oil stoves, but LPG also poses a danger. The dangers contained in gas cylinders cause users to be afraid to check the availability of gas in cylinders because the checking process must be directly close to the gas cylinder. Because of this danger, users do not check gas availability, causing it to run out of gas when cooking. To solve this problem, a system is needed to detect the availability of LPG contents, which can be monitored remotely so that users will feel safe because they are not close to gas cylinders. The condition of gas cylinder availability can be remotely monitored using the internet of things (IoT) method. Therefore, an IoT-based LPG pressure monitoring tool was designed. A tool designed using the MPX-5700AP sensor is useful for detecting gas pressure values in LPG cylinders. IoT is used to monitor LPG pressure using the Blynk application. The buzzer module is a tool for sending sound signals as information on the condition of gas cylinders. The NodeMCU ESP8266 microcontroller processes and sends data to the Blynk application. System testing is carried out in three conditions: full, close to empty, and empty. The results of this test showed an error value of 3.41% and an accuracy rate of 96.59%.